Answer:
Answer:
The graph will be
2 units away from the origin on positive
and three units upward from the origin towards
.
Step-by-step explanation:
Here is a graph attached with it.
To graph
we know that positive
is a
shaped from the origin.
Key points:
- To move rightward there must be a negative inside the parentheses.
- And to move upward we must have positive
.
If we have to move towards
then we must have negative inside it.
And if we have to move upward in
positive we must have positive constant value.
So the graph will be three units upward and two units rightward with a V-shaped ray.
Answer:
![y=2x^2-4x-8](https://tex.z-dn.net/?f=y%3D2x%5E2-4x-8)
Step-by-step explanation:
<u>Factored form of a parabola</u>
![y=a(x-p)(x-q)](https://tex.z-dn.net/?f=y%3Da%28x-p%29%28x-q%29)
where:
- p and q are the x-intercepts.
- a is some constant.
Given x-intercepts:
Therefore:
![\implies y=a(x-(1+\sqrt{5}))(x-(1-\sqrt{5}))](https://tex.z-dn.net/?f=%5Cimplies%20y%3Da%28x-%281%2B%5Csqrt%7B5%7D%29%29%28x-%281-%5Csqrt%7B5%7D%29%29)
![\implies y=a(x-1-\sqrt{5})(x-1+\sqrt{5})](https://tex.z-dn.net/?f=%5Cimplies%20y%3Da%28x-1-%5Csqrt%7B5%7D%29%28x-1%2B%5Csqrt%7B5%7D%29)
To find a, substitute the given point (4, 8) into the equation and solve for a:
![\implies a(4-1-\sqrt{5})(4-1+\sqrt{5})=8](https://tex.z-dn.net/?f=%5Cimplies%20a%284-1-%5Csqrt%7B5%7D%29%284-1%2B%5Csqrt%7B5%7D%29%3D8)
![\implies a(3-\sqrt{5})(3+\sqrt{5})=8](https://tex.z-dn.net/?f=%5Cimplies%20a%283-%5Csqrt%7B5%7D%29%283%2B%5Csqrt%7B5%7D%29%3D8)
![\implies4a=8](https://tex.z-dn.net/?f=%5Cimplies4a%3D8)
![\implies a=2](https://tex.z-dn.net/?f=%5Cimplies%20a%3D2)
Therefore, the equation of the parabola in factored form is:
![\implies y=2(x-1-\sqrt{5})(x-1+\sqrt{5})](https://tex.z-dn.net/?f=%5Cimplies%20y%3D2%28x-1-%5Csqrt%7B5%7D%29%28x-1%2B%5Csqrt%7B5%7D%29)
Expand so that the equation is in standard form:
![\implies y=2(x^2-x+\sqrt{5}x-x+1-\sqrt{5}-\sqrt{5}x+\sqrt{5}-5)](https://tex.z-dn.net/?f=%5Cimplies%20y%3D2%28x%5E2-x%2B%5Csqrt%7B5%7Dx-x%2B1-%5Csqrt%7B5%7D-%5Csqrt%7B5%7Dx%2B%5Csqrt%7B5%7D-5%29)
![\implies y=2(x^2-x-x+\sqrt{5}x-\sqrt{5}x+\sqrt{5}-\sqrt{5}+1-5)](https://tex.z-dn.net/?f=%5Cimplies%20y%3D2%28x%5E2-x-x%2B%5Csqrt%7B5%7Dx-%5Csqrt%7B5%7Dx%2B%5Csqrt%7B5%7D-%5Csqrt%7B5%7D%2B1-5%29)
![\implies y=2(x^2-2x-4)](https://tex.z-dn.net/?f=%5Cimplies%20y%3D2%28x%5E2-2x-4%29)
![\implies y=2x^2-4x-8](https://tex.z-dn.net/?f=%5Cimplies%20y%3D2x%5E2-4x-8)
Answer:
f = 1, w = 4
Step-by-step explanation:
Given the 2 equations
5w = 23 - 3f → (1)
4f = 12 - 2w (add 2w to both sides )
2w + 4f = 12 ( subtract 4f from both sides )
2w = 12 - 4f → (2)
Multiplying (1) by 4 and (2) by - 3 and adding the result will eliminate f
20w = 92 - 12f → (3)
- 6w = - 36 + 12f → (4)
Add (3) and (4) term by term to eliminate f
14w = 56 ( divide both sides by 14 )
w = 4
Substitute w = 4 into either of the 2 equations and solve for f
Substituting into (1)
5(4) = 23 - 3f
20 = 23 - 3f ( subtract 23 from both sides )
- 3 = 3f ( divide both sides by - 3 )
1 = f
Answer:
![\huge\boxed{x=8;\ y=1\to(8;\ 1)}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7Bx%3D8%3B%5C%20y%3D1%5Cto%288%3B%5C%201%29%7D)
Step-by-step explanation:
![\left\{\begin{array}{ccc}y=x-7&(1)\\5+2y=7&(2)\end{array}\right\\\\\text{Substitute (1) to (2) and solve for x:}\\\\5+2(x-7)=7\qquad\text{use the distributive property}\\\\5+(2)(x)+(2)(-7)=7\\\\5+2x-14=7\\\\2x+(5-14)=7\\\\2x-9=7\qquad\text{add 9 to both sides}\\\\2x-9+9=7+9\\\\2x=16\qquad\text{divide both sides by 2}\\\\\dfrac{2x}{2}=\dfrac{16}{2}\\\\\boxed{x=8}](https://tex.z-dn.net/?f=%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bccc%7Dy%3Dx-7%26%281%29%5C%5C5%2B2y%3D7%26%282%29%5Cend%7Barray%7D%5Cright%5C%5C%5C%5C%5Ctext%7BSubstitute%20%281%29%20to%20%282%29%20and%20solve%20for%20x%3A%7D%5C%5C%5C%5C5%2B2%28x-7%29%3D7%5Cqquad%5Ctext%7Buse%20the%20distributive%20property%7D%5C%5C%5C%5C5%2B%282%29%28x%29%2B%282%29%28-7%29%3D7%5C%5C%5C%5C5%2B2x-14%3D7%5C%5C%5C%5C2x%2B%285-14%29%3D7%5C%5C%5C%5C2x-9%3D7%5Cqquad%5Ctext%7Badd%209%20to%20both%20sides%7D%5C%5C%5C%5C2x-9%2B9%3D7%2B9%5C%5C%5C%5C2x%3D16%5Cqquad%5Ctext%7Bdivide%20both%20sides%20by%202%7D%5C%5C%5C%5C%5Cdfrac%7B2x%7D%7B2%7D%3D%5Cdfrac%7B16%7D%7B2%7D%5C%5C%5C%5C%5Cboxed%7Bx%3D8%7D)
![\text{Substitute it to (1):}\\\\y=8-7\\\\\boxed{y=1}](https://tex.z-dn.net/?f=%5Ctext%7BSubstitute%20it%20to%20%281%29%3A%7D%5C%5C%5C%5Cy%3D8-7%5C%5C%5C%5C%5Cboxed%7By%3D1%7D)
So a triangular prisim is like a triangle stacked on top of x number of identical triangles making a height, like a piece of paper made into a stack
so
basically find the area of each side and add
look at diagram/attachment
find area of triangle
1/2 b times h= area of 1 triangular face
multiply by 2 because 2 sides so 1/2 times 2 b times h=b times h
then 3 other sides
find area of each side and add
areas=(H times B)+(H times c)+(H times a)
so SA=(b times H)+(H times B)+(H times c)+(H times a)